2021
DOI: 10.1021/acsomega.0c05505
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Thermal Effect during Gas Adsorption and Desorption on the Coal Surface

Abstract: The thermal effect of coal adsorption/desorption gas is very important for understanding the evolution of coal temperature and interaction between coal and gas during coal and gas outburst. The pressure difference between the high gas pressure area in front of the working face and the low gas pressure area near the coal wall may affect the adsorption/desorption thermal effect. In order to reveal the characteristics of the coal adsorption/desorption gas thermal effect at different pressure differences, a thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Durucan et al proposed that the matrix swelling caused by CO 2 injection has a serious effect on the permeability of coal by carrying out the deformation test of CO 2 adsorption on coal samples and found that the swelling of coal increases with the increase of the coal rank, which is considered to be related to the larger adsorption capacity of high rank coal. The temperature of coal increases in the process of gas adsorption and decreases when desorption. , This change is more obvious especially in the case of coal and gas outburst . When the temperature of the coal seam rises, the adsorption capacity of CBM changes. , Killingley and co-workers showed that the methane adsorption capacity decreased by 0.12 cm 3 /g when the temperature increased by 1 °C at 5 MPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Durucan et al proposed that the matrix swelling caused by CO 2 injection has a serious effect on the permeability of coal by carrying out the deformation test of CO 2 adsorption on coal samples and found that the swelling of coal increases with the increase of the coal rank, which is considered to be related to the larger adsorption capacity of high rank coal. The temperature of coal increases in the process of gas adsorption and decreases when desorption. , This change is more obvious especially in the case of coal and gas outburst . When the temperature of the coal seam rises, the adsorption capacity of CBM changes. , Killingley and co-workers showed that the methane adsorption capacity decreased by 0.12 cm 3 /g when the temperature increased by 1 °C at 5 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature of coal increases in the process of gas adsorption and decreases when desorption. 14,15 This change is more obvious especially in the case of coal and gas outburst. 16 When the temperature of the coal seam rises, the adsorption capacity of CBM changes.…”
Section: Introductionmentioning
confidence: 99%
“…Yi et al 9 proposed a concentration-based extraction pressure adjustment method to improve the gas utilization rate. Chen et al 10 and Hao et al 11 established a gas–solid coupling model to study the gas extraction law of the three-dimensional model of a coal seam. Liu et al 12 proposed a theoretical model to describe gas desorption, diffusion, and flow around a drainage hole based on field experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The gas drainage technology and gas migration law complement each other. 5 12 Thick and high-gas coal seams are widespread in the United States, Australia, and China. 13 16 However, there are a few pieces of research on the gas extraction technology for slice mining of extra-thick coal seams that need to be carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Gas prevention is an important guarantee for safe and efficient production in mines, and as the mining depth increases, coal mining will face more and more gas prevention problems in the future. At present, various technologies have been developed for gas extraction, such as coal seam preextraction, pressure relief gas drainage in the adjacent layer, bottom drainage roadway extraction, high alley pumping extraction, high level borehole extraction, goaf buried pipe extraction, large diameter drilling extraction, and so forth. The gas drainage technology and gas migration law complement each other. Thick and high-gas coal seams are widespread in the United States, Australia, and China. However, there are a few pieces of research on the gas extraction technology for slice mining of extra-thick coal seams that need to be carried out.…”
Section: Introductionmentioning
confidence: 99%